Perspectives on a Big Data Application: What Database Engineers and IT Students Need to Know - Erturk, E.; Jyoti, K. (Engineering, Technology & Applied Science Research, 2015)
Cloud Computing and Big Data are important and related current trends in the world of information technology. They will have significant impact on the curricula of computer engineering and information systems at universities and higher education institutions. Learning about big data is useful for both working database professionals and students, in accordance with the increase in jobs requiring these skills. It is also important to address a broad gamut of database engineering skills, i.e. database design, installation, and operation. Therefore the authors have investigated MongoDB, a popular application, both from the perspective of industry retraining for database specialists and for teaching. This paper demonstrates some practical activities that can be done by students at the Eastern Institute of Technology New Zealand. In addition to testing and preparing new content for future students, this paper contributes to the very recent and emerging academic literature in this area. This paper concludes with general recommendations for IT educators, database engineers, and other IT professionals.